Hubungan Dukungan Keluarga Dengan Kepatuhan Ibu Hamil Dalam Melakukan Antenatal Care Di Puskesmas Kakaskasen - Danu Kurniawan, Cornelius; Rizky Cinanthia, Andita; Giska Kapoh, Mauren (JINTAN: Jurnal Ilmu Keperawatan, 2025)
Pregnancy is a natural and physiological process. Every woman who has healthy reproductive organs, has menstruated, and has sexual relations with a healthy man has a high probability of pregnancy (Nugrawati & Amriani, 2021). The purpose of this study is to know the relationship between family support and the compliance of pregnant women in antenatal care examination at Kakaskasen Health Center. This study used Cross Sectional design. The population in this study was 53 pregnant women while the sample in the study as many as 22 pregnant women in trimester III, and sampling technique used was random sampling techniques. The results found that most of respondents have good family support with good maternity compliance which is 12 respondents (54.5%). The data were collected through maternity compliance questionnaires with a value of Cronbach’s alpha = 0.749 and pregnant woman's compliance questionnaires with a value of Cronbach’s alpha = 0.756. From the analysis of the two variables above using Spearman Rho statistical tests, the significant values of the relationship of the two variables was (p)= 0.000 which is less than 0.05. It indicates a relationship between family support and compliance of pregnant women in Kakaskasen Health Center, while the correlation coefficient (r)= 0.821 indicates a very strong level of relationship between the dependent and the independent varibles.